IEA International Computer and Information Literacy Study 2018 Assessment Framework - Fraillon, Julian (Springer Nature, 2019)
This open access book presents the assessment framework for IEA's International Computer an Information Literacy Study (ICILS) 2018, which is designed to assess how well students are prepared for study, work and life in a digital world. The study measures international differences in students' computer and information literacy (CIL): their ability to use computers to investigate, create, participate and communicate at home, at school, in the workplace and in the community. Participating countries also have an option for their students to complete an assessment of computational thinking (CT). The ICILS assessment framework articulates the basic structure of the study, providing a description of the ﬁeld and the constructs to be measured. This book outlines the design and content of the measurement instruments, sets down the rationale for those designs, and describes how measures generated by those instruments relate to the constructs. Hypothesized relations between constructs provide the foundation for some of the analyses that follow. Above all, the framework links ICILS to other similar research, enabling the contents of this assessment framework to combine theory and practice in an explication of both the 'what' and the 'how' of ICILS.